Who let the dogs out?: the effect of parliamentary scrutiny on compliance with EU law - Finke, Daniel; Dannwolf, Tanja (Journal of European public policy, 2015)
Recently, it has been argued that the scrutiny of European law proposal by national parliaments contributes to speeding up the implementation of EU law. To test this argument, we study the effect of parliamentary scrutiny on Germany's compliance with all directives adopted between 1999 and 2012. The results are mixed: on the one hand, parliamentary scrutiny successfully transfers necessary deliberations from the implementation stage to the policy-making stage. As a consequence, we observe faster implementation of complex and controversial policies. On the other hand, parliamentary scrutiny carries the risk of triggering conflict and of forcing early commitments by actors who might otherwise have remained passive observers. As a consequence, parliamentary scrutiny may even delay implementation of EU law by waking the proverbial ‘sleeping dogs'.